Motivasi Petani dalam Menerapkan Sistem Tanam Jajar Legowo 2:1 di Subak Karang Dalem, Desa Bongkasa Pertiwi, Kecamatan Abiansemal, Kabupaten Badung - KRISNANDARI, AYU DWI; PUTRA, I GEDE SETIAWAN ADI; ANGGRENI, I GST. A.A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Motivation Of Farmers In Applying Legowo Jajar Planting System 2: 1 In Subak Karang Dalem, Bongkasa Pertiwi Village, Abiansemal District, Badung District. Legowo row planting system is a cropping pattern that alternates between two or more (usually two or four) rows of rice plants and one blank row. motivation is a psychological process, both internal and external that is an important determinant of individual performance. The purpose of this study was to analyze the motivation of subak farmers to apply the jajar legowo planting system in Subak Karang Dalem. The population in this study were all members of Subak Karang Dalem, amounting to 825 people. With a sample of respondents in this study, there were 42 farmers from Subak Karang Dalem, Bongkasa Village, Abiansemal District, Badung Regency. Data collection methods used in this study were structured interviews, literature studies, and the documentation and instruments used were questionnaires. The analysis techniques used in this study include descriptive analysis and quantitative analysis. The results showed that intrinsic motivation with extrinsic motivation had an interrelated relationship with a coefficient value of 0.827. The level of success of farmers divided into 3, namely technical success of 3.58 with low category, economic success of 3.94 with low category, and social success of 4.23 with medium category. Motivation with the success of farmers has a related relationship, the higher the motivation of farmers, the higher the success of farmers, and vice versa with a coefficient of 0.755.